Pertanggungjawaban Pemilik Gedung Mall atas Kerusakan Gedung Hingga Pengunjung Mall Meninggal Dunia - Eka Andrean Ramadhan; Anak Agung Sagung Laksmi Dewi; Ni Made Sukaryati Karma (Jurnal Interpretasi Hukum, 2022)
This study aims to analyze and describe the regulations for criminal liability of mall building owners for building damage that causes mall visitors to die and criminal sanctions that ensnare mall building owners. The research method used is normative legal research, this writing study is based on legal materials and literature, which are the stages in obtaining legal rules or norms. The analysis of legal materials is a descriptive-analytical analysis. The results of the study indicate that the responsibility of building owners has been listed in the civil law code where the owner must be responsible if the building collapses causing people to become victims, so they must carry out maintenance and maintenance of the building so that there is no damage that causes the collapse of the mall building.